Keamanan Komputer Dalam Novel Spammer Karya Ronny Mailindra - I Gede Widiantara; Eva Dwi Kurniawan (Jurnal Publikasi Teknik Informatika, 2024)
The threats related to computer viruses have become a highly significant issue in the era of technology. Data and computer system security are the primary concerns in various sectors, including businesses, government, and individuals. This research aims to examine how computer viruses are spread and how computer security works within the novel Spammer by Ronny Mailindra. The method used is hermeneutics. Based on the analysis and discussion, the findings reveal 1) Spyware for mobile phones, 2) Trojans, 3) Viruses, 4) Digital footprints, 5) Remote SSH. In the novel Spammer it is depicted that computer viruses are commonly disseminated through email spam, and one of the network security protocols that proves challenging to breach is the Secure Shell Protocol (SSH).